Paradigma Thomas Kuhn : Revolusi Ilmiah dan Penerapan dalam Bimbingan Konseling - Pristiwanti, Yuwanita (Universitas Muria Kudus, 2023)
A paradigm is referred to as what we will obtain from examining the behavior of members of a scientific community that has been previously determined and used as a constellation of beliefs, values, techniques, etc. that have been carried out by members of that scientific community. recognized community. This research aims to complement previous research, this research focuses on discussion, namely research that examines